CONSTRUCTING A HIERARCHICAL PYRAMID OF CORPORATE SOCIAL RESPONSIBILITY: A MODEL FROM LEGAL AND ECONOMIC TO SPIRITUAL OBLIGATION - Sukoharsono, Eko Ganis; Widhianingrum, Purweni; Purba, Alan Smith (Accounting Department,, 2021)
Purpose — The objective of the study is to construct a hierarchical pyramid of corporate social responsibility which provides a new model from economic to spiritual obligation of a corporation. Design/methodology/approach — The research method of the study utilizes an imaginary dialogue of the postmodernist paradigm. The imaginary dialogue is used of two persons which are an accountant and a stockholder of a company.Findings — The result of the study is a hierarchical pyramid of corporate social responsibility constructed. The study also defines detail of the levels. Firstly, the legal obligation is the basic obligation which a corporation has responsible for obeying the law. Secondly, the economic obligation is a corporate responsibility for accelerating economically and profitably for the corporation going concerned. Thirdly, the social philanthropic obligation is responsible for caring society as a large. Fourthly, the environmental obligation is responsible for preserving natural environments like a large. Lastly, the spiritual obligation is responsible for being fully aware of the internal corporation, society, environments, state, and God. Practical Implications — The hierarchical pyramid is a model of corporation obligations started from the level of legal, economic, Social philanthropic, environmental, and spiritual obligations. Originality/value — The model of this study is derived from the analysis of corporate obligation using a postmodernist paradigm.Keywords corporate, economics, postmodernism, economic obligation, spiritual obligationPaper Type Research Paper.